MicroRNA‐124 Regulates Cardiomyocyte Differentiation of Bone Marrow‐Derived Mesenchymal Stem Cells Via Targeting STAT3 Signaling123. (24th July 2012) - Cai, Benzhi; Li, Jianping; Wang, Jinghao; Luo, Xiaobin; Ai, Jing; Liu, Yanju; Wang, Ning; Liang, Haihai; Zhang, Mingyu; Chen, Nan; Wang, Gang; Xing, Shu; et al.
Abstract: Accumulating evidence demonstrated that bone marrow‐derived mesenchymal stem cells (BMSCs) may transdifferentiate into cardiomyocytes and replace apoptotic myocardium so as to improve functions of damaged hearts. However, little information is known about molecular mechanisms underlying myogenic conversion of BMSCs. microRNAs as endogenous noncoding small molecules function to inhibit protein translation post‐transcriptionally by binding to complementary sequences of targeted mRNAs. Here, we reported that miR‐124 was remarkably downregulated during cardiomyocyte differentiation of BMSCs induced by coculture with cardiomyocytes. Forced expression of miR‐124 led to a significant downregulation of cardiac‐specific markers—ANP, TNT, and α‐MHC proteins as well as reduction of cardiac potassium channel currents in cocultured BMSCs. On the contrary, the inhibition of endogenous miR‐124 with its antisense oligonucleotide AMO‐124 obviously reversed the changes of ANP, TNT, and α‐MHC proteins and increased cardiac potassium channel currents. Further study revealed that miR‐124 targeted the 3′UTR of STAT3 gene so as to suppress the expression of STAT3 protein but did not affect its mRNA level. STAT3 inhibitors AG490, WP1066, and S3I‐201 were shown to attenuate the augmented expression of ANP, TNT, α‐MHC, GATA‐4 proteins, and mRNAs in cocultured BMSCs with AMO‐124 transfection. Moreover, GATA‐4 siRNA reduced the expression of ANP, TNT, α‐MHC, and GATA‐4 proteins but did not impact STAT3 protein in cocultured BMSCs, indicating GATA‐4 serves as an effector of STAT3. In summary, we found that miR‐124 regulated myogenic differentiation of BMSCs via targeting STAT3 mRNA, which provides new insights into molecular mechanisms of cardiomyogenesis of BMSCs. STEM CELLS 2012;30:1746–1755